Estimating the cost of achieving basic water, sanitation, hygiene, and waste management services in public health-care facilities in the 46 UN designated least-developed countries: a modelling study. Issue 6 (June 2022) - Chaitkin, Michael; McCormick, Samantha; Alvarez-Sala Torreano, Jorge; Amongin, Irene; Gaya, Silvia; Hanssen, Odd N; Johnston, Richard; Slaymaker, Tom; Chase, Claire; Hutton, Guy; Montgomery, Maggie
Summary: Background: An alarming number of public health-care facilities in low-income and middle-income countries lack basic water, sanitation, hygiene (WASH), and waste management services. This study estimates the costs of achieving full coverage of basic WASH and waste services in existing public health facilities in the 46 UN designated least-developed countries (LDCs). Methods: In this modelling study, in-need facilities were quantified by combining published counts of public facilities with estimated basic WASH and waste service coverage. Country-specific per-facility capital and recurrent costs to deliver basic services were collected via survey of country WASH experts and officials between Sept 24 and Dec 24, 2020. Baseline cost estimates were modelled and discounted by 5% per year. Key assumptions were adjusted to produce lower and upper estimates, including adjusting the discount rate to 8% and 3% per year, respectively. Findings: An estimated US$6·5 billion to $9·6 billion from 2021 to 2030 is needed to achieve full coverage of basic WASH and waste services in public health facilities in LDCs. Capital costs are $2·9 billion to $4·8 billion and recurrent costs are $3·6 billion to $4·8 billion over this time period. A mean of $0·24–0·40 per capita in capital investment is needed each year, and annual operations and maintenance costs are expected to increase from $0·10 in 2021 to $0·39–0·60 in 2030. Waste management accounts for the greatest share of costs, requiring $3·7 billion (46·6% of the total) in the baseline estimates, followed by $1·8 billion (23·1%) for sanitation, $1·5 billion (19·5%) for water, and $845 million (10·7%) for hygiene. Needs are greatest for non-hospital facilities ($7·4 billion [94%] of $7·9 billion) and for facilities in rural areas ($5·3 billion [68%]). Interpretation: Investment will need to increase to reach full coverage of basic WASH and waste services in public health facilities. Financial needs are modest compared with current overall health and WASH spending, and better service coverage will yield substantial health benefits. To sustain services and prevent degradation and early replacement, countries will need to routinely budget for operations and maintenance of WASH and waste management assets. Funding: WHO (including underlying grants from the governments of Japan, the Netherlands, and the UK), World Bank (including an underlying grant from the Global Water Security and Sanitation Partnership), and UNICEF. Translations: For the Arabic, French and Portuguese translations of the abstract see Supplementary Materials section.